Evaluation of the Performance Business of Hand Line Yellowfin Tuna at Bacan Beach Fishery Port South Halmahera Regency - Masiyah, Siti; Nisaa, Khoirun; Melmambessy, Edy H.P.; Ali Lutfi, Mohammad (Agrikan Jurnal Agribisnis Perikanan, 2021)
Fiddler crab (Uca spp.) one of the crabs that inhabit the intertidal area, especially the mangrove with the sandy and muddy substrate. This study aims to determine the population and microhabitat of Uca spp. in Payum beach Merauke. Research was conducted in June to July 2019 at the research transect 3 sampling points which was determined by purposive sampling method. Samples were taken by making the square plot of 1 x 1 m is placed at the point of the study and then the substrate was dug up to a depth of 30 cm. Crab that has been collected, then identified and classified. Samples crab then fixation with 70% alcohol. A total population of 6 species of crab Uca found in mangrove areas Payum beach Merauke is Uca tetragonon, Uca annulipes, Uca coarctata, Uca crassipes, Uca signata and Uca dussumieri. Of all types are found crab Uca have each habitat type living. The highest density was found in the species of Uca signata 32 ind/mÂ² and the smallest species of Uca dussumieri ie 11 ind/mÂ². The diversity index value is 1.74. The evenness index is 0.97. The dominant index is 0.18 and the morisita index is clustered on the species Uca signata. So it can be concluded that the environmental microhabitat conditions of the research location is support the survival of the fiddler crab (Uca spp.).